2008
DOI: 10.1038/jhh.2008.146
|View full text |Cite
|
Sign up to set email alerts
|

The study of insulin resistance and soluble intercellular adhesion molecule-1 in normotensive adolescents with a family history of hypertension

Abstract: To investigate the changes of insulin resistance and soluble intercellular adhesion molecule-1 (sICAM-1) in normotensive adolescents with a family history of hypertension (FH) and to analyse the related factors. The study included 142 normotensive adolescents aged 13-15 years. On the basis of an FH, the samples were divided into positive FH (FH þ group) and negative FH groups (FH À group). Anthropometric measurements included height, weight, waist circumference (WC) and blood pressure (BP). Blood samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…in a study done by Fu-zai et al, indicate that insulin resistance and endothelial activation were found in normotensive adolescents with a family history. 22 Whereas, in a study done by Covelli MM et al to determine the relationship of blood pressure and cortisol reactivity to family history of hypertension of African American adolescents the blood pressure reactivity of the family history positive group was significantly different than with no family history group (P = 0.0338). Cortisol levels for the total group were markedly elevated (19 nmol/dL) and there was no significant difference in reactivity.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…in a study done by Fu-zai et al, indicate that insulin resistance and endothelial activation were found in normotensive adolescents with a family history. 22 Whereas, in a study done by Covelli MM et al to determine the relationship of blood pressure and cortisol reactivity to family history of hypertension of African American adolescents the blood pressure reactivity of the family history positive group was significantly different than with no family history group (P = 0.0338). Cortisol levels for the total group were markedly elevated (19 nmol/dL) and there was no significant difference in reactivity.…”
Section: Discussionmentioning
confidence: 91%
“…There is a long preclinical phase in the disease where other predictors/biomarkers can be measured [21][22][23][24][25][26][27] , long before changes in blood pressure manifests, which could be studied in future.…”
Section: Discussionmentioning
confidence: 99%
“…25 Vascular inflammation has been demonstrated in arterial hypertension, and inflammationrelated upregulation of endothelial adhesion molecules is an early stage in atherogenesis. 26 Endothelial inflammation has also been suggested to have a role in hypertensive vascular injury and remodelling. 27 Of note, arterial endothelial dysfunction in hypertension often does not improve by acute BP reduction indicating the presence of chronic endothelial changes may be independent of the current shear stress.…”
Section: Endothelial Dysfunction and Bp Controlmentioning
confidence: 99%